AMPA-receptors and fast synaptic transmission in the brain - Cull-Candy, Stuart (Henry Stewart Talks, 2015)
The fast component of excitatory synaptic transmission in the brain mediated by AMPARs, Functionally distinct AMPAR subtypes are involved in transmission (importance of topology), How AMPAR diversity shapes transmission (implications of differential distribution and plasticity), How AMPAR structure affects its behaviour and properties, Role of auxiliary AMPAR proteins (stargazin) in controlling AMPAR properties and diversity